Economic Stimulation of Household Business Activity in the Economy of Kazakhstan - N. N. Nurmukhametov; A. E. Belousova; G. K. Utarbayeva; Z. M. Bulakbay (Экономика: стратегия и практика, 2022)
The purpose of the scientific article is to study the problem of increasing the business activity of the rural population in the conditions of the «new» economy of Kazakhstan and to develop proposals for stimulating the economic activity of personal subsidiary farms. The use of classical methods of scientific cognition and literature review allowed us to study the theoretical foundations and reveal the economic essence of the categories of «business activity» regarding its applicability to the economy of the household. Based on the macroeconomic analysis, the main indicators and trends of the development of the economy of Kazakhstan were studied, the share of the agricultural economy in the country’s GDP was determined. It is revealed that the agricultural economy in the overall structure of the national economy can become a priority industry in the long term, which is justified by the effectiveness of the activities of agribusiness entities in conditions of developed competition. It is confirmed that 58% of the rural population are self-employed, and 46% of the population cannot provide for their basic needs, since the only source of income is transfer payments (social benefits) from the state budget. It is determined that the inflation rate has a significant impact on the real income of households. The model of economic stimulation of the business activity of personal subsidiary farms is presented, taking into account their peculiarities of formation and development as a form of agribusiness organization, which clearly affects the agricultural economy of Kazakhstan.